Colon hernias: surgical tactics - Suiffet, Walter; Croci, Fabio (Cirugía del Uruguay, 1984)
Analysis · oJ the different problems of the surgical treatment of colon hernias, with specífic mention of the rísks implied in this variety. Visceral aggression and vascular aggression are the most important factors causing complications in this surgery.